A novel compound heterozygous mutation of COL6A3 in Chinese patients with isolated cervical dystonia - Wu, Rui; Dou, Weikang; Zhou, Huimin; Shi, Ming (Frontiers in Neurology, 2023)
Background: The etiology and pathogenesis of idiopathic dystonia still remain obscure. Recent studies revealed that compound heterozygous mutations in collagen type VI alpha3 gene COL6A3 may cause recessive isolated dystonia (DYT)-27. However, whether COL6A3 mutations are associated with Chinese patients with isolated dystonia is not as yet reported. Methods: Forty-five Chinese patients with isolated cervical dystonia were recruited and their blood DNA samples were subjected to whole-exome sequencing. The potential causal variants of COL6A3 were identified based on the criteria of American College of Medical Genetics and Genomics and by the prediction softwares. Results: Among 45 isolated cervical dystonia patients, 18 patients (10 females and 8 males) were found to have 7 potential causal variants in the COL6A3 gene. Among these variants, a compound heterozygous mutation was found in one patient. One allele had a c.1264G>A mutation in exon 4 that resulted in amino acid substitution of methionine for valine at codon 422 (p.Val422Met) and the other a c.8965+9G>A involving a splicing change in exon 40. In addition, other 5 missense variants, including c.958G>A (p.Ala320Thr), c.1478T>C (p.Val493Ala), c.1597C>T (p.Arg533Cys), c.1762G>A (p.Asp588Asn) and c.4912G>A (p.Ala1638Thr) were identified as well. Conclusion: We identified a novel deleterious compound heterozygous mutation as well as 5 missense variants in the COL6A3 gene of Chinese patients with cervical dystonia. These findings may expand the spectrums of COL6A3 genotype in isolated dystonia.